New insights into the genetic mechanism of IQ in autism spectrum disorders - Wang, Harold Z.; Qin, Hai-De; Guo, Wei; Samuels, Jack; Shugart, Yin Y. (Frontiers in Genetics, 2013)
Autism spectrum disorders (ASD) is a complex condition with a number of underlying subtypes with different symptoms and presumably different genetic causes. One important difference between these sub-phenotypes is cognition. Some forms of ASD such as Asperger’s keep cognitive development intact while the majority does not. In this study we explored genetic factors that might account for this difference. Using a case-control study based on IQ status in 1657 ASD probands, we analyzed both common and rare variants provided by the Autism Genome Project consortium via dbGAP, identified a set of genes, among them SYT1L and KIAA0319L, that are strongly associated with IQ within a population of ASD patients.